A Patient-Relevant Measurement Strategy to Assess Clinical Benefit of Novel Therapies for Non-metastatic Cutaneous Squamous Cell Carcinoma - Diana Rofail; Anna Ciesluk; Teya Lovell; Patrick Marquis; Matthew G. Fury; Chieh-I Chen (Oncology and Therapy)
Abstract Introduction Although cutaneous squamous cell carcinoma (CSCC) is the second most common type of skin cancer, research describing the patient experience is limited. This study sought to create a conceptual model of non-metastatic disease, to assess patient-reported outcome (PRO) instruments commonly used in CSCC against this model, and to develop a patient-relevant measurement strategy for evaluating the benefit of new therapies. Methods Researchers conducted a literature review, a review of patient blogs, and interviews with dermatologists to draft the conceptual model. A total of 22 patients with CSCC participated in 60-min phone interviews, which were subsequently transcribed, coded, and analyzed; the conceptual model was then updated. PRO instruments used in CSCC were assessed for content validity on the basis of this. Results The CSCC patient experience includes physical symptoms, psychological impacts, and behavior changes. Existing PRO instruments were assessed against the conceptual model using targeted subdomains considered to be relevant for assessing clinical benefit. Four modules of the FACE-Q® Skin Cancer instrument, plus de novo items developed for concepts not assessed by the FACE-Q® [lesion symptoms, negative treatment effects (including symptomatic), and experience of care], provide the best coverage for the concepts of interest hypothesized to show the benefit of novel treatments. Conclusions This research provides a comprehensive understanding of the experience of patients with non-metastatic CSCC, and the effects of its treatment. It also identifies unmet needs in a subgroup of patients reporting negative treatment experiences. Further cognitive debriefing and psychometric analysis of de novo items are warranted for applications in clinical research.